Mordida Abierta Anterior - García, César A. (Revista Estomatología, 2004)
Open bites can be related to skeletal, dental, and soft tissue effects and generally obey to a combination of these factors (multifactorial). Sometimes it is possible to identify the pecific etiologic factors, but especially in open-bite cases of skeletal origin, the factors responsible for the malocclusion can not be identified easily. Treatment of patients with open bite must be performed early to be successful. Otherwise the opportunity for growth modification could be lost, leaving surgical correction as the only possible treatment. Control of the vertical dimension is considered the most important factor in the treatment of open bite malocclusions and the molar intrusion is the primary treatment objective to achieve these treatment goals. Various treatment modalities have been proposed for the correction of anterior open bites. A conventional approach is to inhibit the vertical maxillary growth or to intrude maxillary molars with headgear. Other treatment devices reported include vertical-pull chin-ups, functional appliances, bite-blocks, tongue cribs, magnets, multi loop edgewise arch wires (MEAW therapy) miniplate anchorage and various orthognathic surgery combinations. Relationship between temporomandibular joint dysfunction and open bite is not clear.